Functional Outcomes at 90 Days in Octogenarians Undergoing Thrombectomy for Acute Ischemic Stroke: A Prospective Cohort Study and Meta-Analysis - Sharobeam, Angelos; Cordato, Dennis John; Manning, Nathan; Cheung, Andrew; Wenderoth, Jason; Cappelen-Smith, Cecilia (Frontiers in Neurology, 2019)
Background: Elderly patients account for 30% of acute ischemic stroke (AIS) but are under-represented in randomized controlled trials of endovascular thrombectomy (EVT). To date, meta-analysis of “real world” observational studies focusing on 90-day outcomes between patients ≥80 and <80 years have been limited to small numbers undergoing EVT with older generation devices. Methods: The present study is a retrospective analysis of a prospectively collected patient cohort who received EVT for anterior cerebral circulation AIS at an Australian centre over 2.5-years. The study aims to determine (i) the proportion of good 90-day functional outcomes (modified Rankin Scale mRS 0-2) in patients ≥80 compared with <80 years (ii) prognostic factors influencing 90-day outcome in patients ≥80 years and (iii) a comparison of our data to those previously reported in the literature using a meta-analysis of outcomes and mortality in observational studies using second generation stent retrievers. Results: We analyzed 2387 patients (≥80 years, n=649; <80 years, n=1738) from 14 studies including our study (≥80 years, n=71; <80 years, n=110). 28% of our elderly cohort and 30% of the pooled meta-analysis cohort achieved good 90-day functional outcomes compared to 55% and 52%, respectively of younger patients. 27% of our elderly cohort and 26% of the meta-analysis elderly cohort died compared to 16% and 15%, respectively of younger patients. Higher baseline NIHSS correlated with poor prognosis in the elderly. Conclusion: EVT has less favorable outcomes in elderly patients. However, results are better than historical AIS outcomes providing further support for EVT in the elderly.